Hipertensi Arteri Pulmonalis - Frits R.W. Suling (Majalah Kedokteran UKI, 2010)
Abstrak Hipertensi arteri pulmonalis (HAP) adalah sindroma yang ditandai oleh restriksi sirkulasi di arteri pulmonalis, sehingga menyebabkan peningkatan tahanan vaskular pulmoner dan gagal jantung kanan. Sindroma tersebut adalah penyakit yang jarang. Berbagai penyakit dasar telah diketahui sebagai penyebab HAP termasuk diturunkan secara genetik. Di tingkat molekular diketahui terjadi ketidakseimbangan antara proliferasi dan apoptosis sel. Secara mikroskopis kelainannya dapat dilihat pada otot polos, sel endotel dan adventitia pembuluh darah. Ketidak seimbangan antara vasokonstriksi dan dilatasi pembuluh darah menjadi dasar pemberian terapi HAP saat ini. Kata kunci: sesak, edema, asites, gagal jantung kanan Abstract Pulmonary arterial hypertension (PAH) is a syndrome due to restricted flow through the pulmonary arterial circulation. It is resulting in the increase of pulmonary vascular resistance and ultimatelyin right heart failure. Pulmonary arterial hypertension considered as a rare disease. Multiple pathogenic pathways have beenimplicated in the development of PAH, including those at themolecular and the genetic levels. Furhermore, it is known that the imbalance of proliferation and apoptosis plays an important role in the pathogenesis of PAH. Microscopically the result of the imbalance between cell proliferation and apopotosis is appears in the smooth muscle, endothelialcells and the adventitia of the blood vessels. The imbalance in the vasoconstrictionvasodilatationmilieu has served as the basic for the current medical therapy. Key Words : dyspnea, aedema, ascites, right ventricle failure